Evidenciação contábil dos ativos intangíveis: um estudo das empresas brasileiras de 2010 a 2021 classificadas no Índice Bovespa - Dias, Aline Mariane (2023)
With the amendments to law nº 6.404/76, imposed by laws nº 11.638/07 and 11.941/09, a new balance sheet structure began to be adopted. In view of the new practices held since then and considering the influence of Intangible Assets on the business strategy, this study aims to analyze the information on Intangible Assets evidenced in the financial statements of the companies with the highest trading volume on B3 disclosed in the period of 2010 to 2021. The study sample is composed of 75 companies classified in the Bovespa Index on April 20, 2022. The research is characterized as a theorical-empirical descriptive study with a qualitative and quantitative approach through documental analysis of the financial statements of organizations researched. The results show that 24% of the surveyed companies presented just a single item in Intangible Assets throughout the analyzed period and the accounting account that was most presented by the companies was the Software. Intangible Assets represented, on average, 18,11% of the total assets of the companies under analysis and the total of this group increased when compared to first year surveyed